Nostradamus maya 2012 : beyond the mayan prophecy of apocalypses - Carter, Spencer (Mumbai : Shree Book Centre, 2010)
Examines the ancient Mayan significance attached to the year 2012, and the potential relevance to people living today
Keywords: Two thousand twelve, A.D.; Mayas -- Prophecies -- Miscellance